Quṣayr ʻAmra : art and the Umayyad elite in late antique Syria - Fowden, Garth (University of California Press, 2004)
The remarkable frescoes of Quṣayr ʻAmra were probably painted in the middle of the 8th century for a Muslim Arab prince. However many problems remain with regard to the date, the patron & even the meaning of the often erotic scenes. Garth Fowden explores this treasure from the Syrian Desert.
Keywords: Qusayr ʻAmrah (Jordan : Dwelling); Quṣayr ʻAmra (Jordanie); Mural painting and decoration, Umayyad -- Jordan -- Foreign influences.; Arabic poetry -- 622-750 -- History and criticism.; Poésie arabe -- 622-750 -- Histoire et critique.; ART -- Graffiti & Street Art.; HISTORY -- Ancient -- General.; Arabic poetry; Jordan; 622 - 750; Humaniora -- Kunst.; Criticism, interpretation, etc.